2007
DOI: 10.1186/1471-244x-7-27
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and perceptions of electroconvulsive therapy among psychiatric patients: a cross-sectional survey from teaching hospitals in Karachi, Pakistan

Abstract: Background: Electroconvulsive therapy (ECT) is shown to be effective in many psychiatric illnesses, but its distorted projection by the Pakistani media and its unregulated use by many physicians across the country have adversely affected its acceptability. Given this situation we aimed to assess the awareness and perceptions regarding ECT as a treatment modality among the psychiatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 21 publications
3
28
1
Order By: Relevance
“…However, attitudes toward the treatment did not differ between the 2 patient groups. Somewhat similar results were obtained in a study from Pakistan, 19 another country where ECT seems to be used rather infrequently. Consequently, about a quarter of the patients in this study had never heard of ECT and only 25 of the 190 patients interviewed had received the treatment.…”
Section: Discussionsupporting
confidence: 88%
“…However, attitudes toward the treatment did not differ between the 2 patient groups. Somewhat similar results were obtained in a study from Pakistan, 19 another country where ECT seems to be used rather infrequently. Consequently, about a quarter of the patients in this study had never heard of ECT and only 25 of the 190 patients interviewed had received the treatment.…”
Section: Discussionsupporting
confidence: 88%
“…Similar results were found in a survey conducted in Switzerland, which demonstrated that only 1.2% of a representative sample of the public (n = 1737) was in favor of ECT use and 57% considered it a harmful treatment [110]. A strong negative opinion about ECT was noted in another study conducted in Pakistan, where 39% of surveyed patients thought of the treatment as a cause of severe mental and physical illness and that it was inhumane [111].…”
Section: Public Opinion and Attitudessupporting
confidence: 66%
“…10,16,18,22,23,36 The post-ECT improvement of patients' attitude has been reported in at least 2 similar studies. 23,36 Furthermore, in our study, a comparison of patients'/families' attitude toward ECT, before and after their/their relative patients' experience with ECT, showed a significant improvement in patients' but not in their families' attitude toward ECT after the experience.…”
Section: Patients' and Families' Attitude Before And After Ectmentioning
confidence: 65%